Auditoría administrativa a inplastico Naranjo Hernandez y compañía ubicada en la provincia de Cotopaxi cantón Latacunga del 01 de enero al 31 de diciembre del 2013 - Gallo Velasquez, Dalila Amabel (2016)
The audit management is a test performed to each of the stages of the administrative process in a company .The development of this research was developed based on the fundamental categories, taking quotes from different authors but especially, Benjamin Franklin`s concepts. Research techniques such as observation, interviews and surveys were used; and verification of information from primary sources. Thus it was observed that there is no control in evaluating the staff performance, lack of training employees in different areas of the company and the absence of a thorough process to take new personal on….